PENGARUH PENGGUNAAN MEDIA LEAFLET TERHADAP PENINGKATAN PENGETAHUAN IBU TENTANG PENCEGAHAN STUNTING DI PUSKESMAS PETALING - Savita, Savita; Hastini Jaelani, Sri (JURNAL SMART ANKes, 2024)
Stunting is a chronic condition that describes the stunted growth of children due to long-terml mlalnutrition. Stunting causes physical developmlent disorders but also threatens cognitive developmlent which has an imlpact on reducing children's productivity in adulthood. This study aimls to determline the effect of education with leaflet mledia about stunting on mlothers' knowledge and attitudes about stunting at the Petaling Health Center in Pangkalpinang City. This study uses the Pre-Experimlent research mlethod with one group pretest and post-test design. The samlple was 38 mlothers who had toddlers in the Turun Health Center area in PangkalpinangCity, samlpling was done by purposive samlpling. Analyzed using the Wilcoxon Test. The results of the analysis of the average knowledge before being given education with leaflet mledia about stunting are The average knowledge of mlothers before being given education with leaflet mledia is 4.53 and after being given 7.42. There is an influence of education with leaflet mledia about stunting on mlothers' knowledge about stunting at the PangkalpinangCity Health Center as seen froml the results of the Wilcoxon test with a p value of 0.000 <0.05. It is hoped that research on stunting with leaflet mledia about stunting can be a reference for researchers who want to conduct further research on mlothers' knowledge towards stunting.